Instability of (GATA) n microsatellite loci in the parthenogenetic Caucasian rock lizard Darevskia unisexualis (Lacertidae) - Tokarskaya, O. N.; Martirosyan, I. A.; Badaeva, T. N.; Malysheva, D. N.; Korchagin, V. I.; Darevsky, I. S.; Danielyan, F. D.; Ryskov, A. P. (Molecular genetics and genomics : MGG, 2004)
Mini- and microsatellites, comprising tandemly repeated short nucleotide sequences, are abundant dispersed repetitive elements that are ubiquitous in eukaryotic genomes. In humans and other bisexual species hypervariable mini- and microsatellite loci provide highly informative systems for monitoring of germline and somatic instability. However, little is known about the mechanisms by which these loci mutate in species that lack effective genetic recombination. Here, multilocus DNA fingerprinting was used to study M13 minisatellite and (GATA)n microsatellite instability in the parthenogenetic Caucasian rock lizard Darevskia unisexualis (Lacertidae). DNA fingerprinting of 25 parthenogenetic families, from six isolated populations in Armenia (comprising a total of 84 siblings), using the oligonucleotide (GATA)4 as a hybridization probe, revealed mutant fingerprinting phenotypes in 13 siblings that differed from their mothers in several restriction DNA fragments. In three families (8 siblings), the mutations were present in the germline. Moreover, the mutant fingerprint phenotypes detected in siblings were also present in population DNA samples. No intrafamily variations in DNA fingerprint patterns were observed with the M13 minisatellite probe. Estimates of the mutation rate for (GATA)n microsatellite loci in D. unisexualis showed that it was as high as that seen in some bisexual species, reaching 15% per sibling or 0.95% per microsatellite band. Furthermore, in one case, a somatic (GATA)n microsatellite mutation was observed in an adult lizard. These findings directly demonstrate that mutations in (GATA)n microsatellite loci comprise an important source of genetic variation in parthenogenetic populations of D. unisexualis.